The readiness for industry 4.0 of the Malaysian manufacturing sector: the roles of organization innovation and aging workforce - Rehman, Hafiz Mudassir (2022)
The manufacturing sector is an indispensable part of a country’s economic system. For Malaysia, it not only helps in transmuting raw material to finished goods but also an essential driver to the country’s economic growth. Owing to this sector, Malaysia holds a remarkable position in exports across the world. It is also a principal contributor to the employment of the country. Although, the manufacturing industry is deemed as the backbone of a country’s growth, however, the industry also faces many challenges due to technological advancements due to the industrial revolution known as Industry 4.0. The aim of Industry 4.0 is to realize productivity and improve efficiency. Its potential disruptive technologies are altering the way of work. Correspondingly, it poses challenges for companies to innovate and in analyzing their readiness for Industry 4.0. Thereby, current research aimed to investigate the key role of organization innovation and its enablers including knowledge-oriented leadership and decentralized organization structure. In addition, change in demographics has shaped another snag in the form of an aging workforce for manufacturing companies. Ergo, the moderating role of the aging workforce was gauged in support to readiness for Industry 4.0 by using Structural Equation Modelling (SEM). A quantitative and qualitative methods were adopted to establish the relationships and understanding of variables. Useful responses from manufacturing companies were collected through self-administered questionnaire and interviews. The responses were examined using Smart PLS 3 and ATLAS.ti software. The results highlighted the important dual role of organization innovation for readiness of Industry 4.0. In Addition, Multi-Group Analysis was performed to confirm the importance of different aging workforce groups between organization innovation and readiness for Industry 4.0. Current research contributed to the body of knowledge a detailed vision of Industry 4.0 and its significance for manufacturing sector in Malaysia. The research findings confirmed a noteworthy knowledge concerning high dependency of readiness for Industry 4.0 on organization innovation and moderating effect of aging workforce between them. Additionally, knowledge-oriented leadership was also identified as an enabler of organization innovation through empirical examination. The moderating role of organization innovation is of high interest for keen researchers. Current research provides a directive for practitioners to pave the way for successful implementation of Industry 4.0. For bye, the research outcomes are thought-provoking to national policymakers which can aid in development of impressive policies for Industry 4.0 while considering the vital role of organization innovation and aging workforce. Finally, the findings will benefit the aged workers to contribute and survive in growing economy.